Risk Factors for Spontaneous Abortion in Georgian Population - Manana Makharadze; Revaz Sulukhia; Mzia Tsiklauri; Lali Melia; Iamze Taboridze (European Scientific Journal, ESJ, 2019)
Background: Spontaneous abortion is a difficult problem for reproduction. This leads to the importance of studying risk factors. Since risk factors depend on demographic, ethnic, and environmental conditions of the population. The aim of our explore is to study the risk factors for spontaneous abortions and risk assessment among the population of Georgia. Methods: We retrospectively studied the clinical and laboratory features of 111 patients with identified spontaneous abortions who were treated at the Gudushauri clinic in 2015-2017. The control was carried out in the same period during the outpatient department of the Gudushauri clinic, 103 pregnant women who gave birth to live neonates. Research methods: history, clinical, clinical laboratory, immunological, morphological, bacteriological, ultrasound. The study of the following factors: age, education, family conditions, living conditions, bad habits, activities, working conditions, hereditary factors, accommodation, extragenital diseases, diet, physical activity, sleep hygiene, gynecological history, uterine deformities, medication during pregnancy, the results of a previous pregnancy, pregnancy complications, infections. Results: The risk ofspontaneous abortion increases: Daily travel to long distance OR=4.34(95% CI:1.45-3.03); Stress - OR=6.36(95% CI:2.43-16.66); intermittent sleep - OR=5.72(95%CI:2.15-15.19); Menstrual disorders OR=9.91(95%CI:2.01- 48.94); hypertension OR=15.26(95% CI:1.03-27.24); anemia- OR=4.14(95% I:1.78-9.62); Flu during pregnancy - OR=6.24(95% CI:1.63-23.90); leukocytosis - OR=1.32(95%CI:1.12-1.55) and decrease the placenta location in the base- OR=0.09(95%CI:0.02-0.47). Conclusion: Daily travel to long distance, flu, anemia, leukocytosis, stress, intermittent sleep during pregnancy, menstrual disorders, hypertension are the independent risk factors of spontaneous abortion in Georgian Population, relative chance of spontaneous abortion reduce: placenta at the base. The risk of spontaneous abortion in Georgian population is not determined by relationship status, bad habits and educational factors.